Impact of segmentectomy and lobectomy on non-lung cancer death in early-stage lung cancer patients. (19th September 2022) - Isaka, Tetsuya; Ito, Hiroyuki; Yokose, Tomoyuki; Saito, Haruhiro; Adachi, Hiroyuki; Miura, Jun; Murakami, Kotaro; Rino, Yasushi
Abstract: OBJECTIVES: This study aimed to analyse the risk of death from non-lung cancer after segmentectomy or lobectomy for early-stage lung cancer. METHODS: A total of 1385 patients underwent lobectomy or segmentectomy for clinical stage 0–I primary lung cancer, with no evidence of recurrence after surgery, between January 2008 and December 2018. Risk factors for non-lung cancer deaths (NLCD) were analysed using multivariable logistic regression analysis. The overall survival (OS) of patients with low and high comorbidities who underwent lobectomy and segmentectomy was compared using a log-rank test. RESULTS: Patients with NLCD ( n  = 126) were more likely to have undergone lobectomy than patients with non-recurrence survival ( n  = 1259). Multivariable analysis revealed that age (≥65 years), smoking index (≥600), body mass index (≤18.5 kg/m 2 ), interstitial pneumonia, values for percentage of predicted vital capacity (≤9.4%) and lobectomy were risk factors for NLCD. Patients who underwent segmentectomy had significantly better 5-year OS than those who underwent lobectomy, after propensity score matching (94.6% vs 90.4%, P  = 0.027). Patients with high comorbidities (patients with ≥2 of the following risks: age ≥65 years, smoking index ≥600, body mass index ≤18.5 kg/m 2, Charlson Comorbidity Index ≥1, values for percentage of predicted vital capacity ≤96.4%) who underwent segmentectomy had a better 5-year OS than those who underwent lobectomy (92.8% vs 87.8%, P  = 0.016). However, there was no difference in 5-year OS between segmentectomy and lobectomy in patients with low comorbidities (98.5% vs 97.4%, P  = 0.867). CONCLUSIONS: The impact of lobectomy and segmentectomy on NLCD depends on the extent of the patients' comorbidities. Abstract : Curative-intent anatomical surgical resection is the standard surgical treatment for early-stage primary lung cancer [1], and lobectomy has been recognized as the standard surgical procedure for curing lung cancer [2].